2017
DOI: 10.2334/josnusd.16-0334
|View full text |Cite
|
Sign up to set email alerts
|

Immune receptors CD40 and CD86 in oral keratinocytes and implications for oral lichen planus

Abstract: Lichen planus (LP) is a chronic T-cell-mediated mucocutaneous inflammatory disease that targets stratified epithelia, including those lining the oral cavity. The intraoral variant of LP (OLP) is associated with interferon (IFN)-γ production by infiltrating T lymphocytes; however, the role of epithelial cells in the etiopathogenesis OLP is not completely understood. There is however a growing body of evidence regarding the involvement of epithelial-derived cytokines, immune receptors, and costimulatory molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…30 Overall, the results of this study strongly suggest that CD40 and CD86 may play an important pathophysiologic role in oral inflammatory diseases like OLP. 30 Moreover, a recent study assessed the production of keratinocyte-derived CXCL9/10/11 under basal and inflammatory conditions as well as the role these chemokines may play in the pathogenesis of OLP. 31 This study showed that tissues from OLP patients harboured significantly higher levels of CXCL9/10/11 compared to normal oral mucosa demonstrating that normal oral keratinocytes have the ability to produce chemotactic molecules and mediate T-cell recruitment.…”
Section: Matrix Metalloproteinasessupporting
confidence: 56%
See 4 more Smart Citations
“…30 Overall, the results of this study strongly suggest that CD40 and CD86 may play an important pathophysiologic role in oral inflammatory diseases like OLP. 30 Moreover, a recent study assessed the production of keratinocyte-derived CXCL9/10/11 under basal and inflammatory conditions as well as the role these chemokines may play in the pathogenesis of OLP. 31 This study showed that tissues from OLP patients harboured significantly higher levels of CXCL9/10/11 compared to normal oral mucosa demonstrating that normal oral keratinocytes have the ability to produce chemotactic molecules and mediate T-cell recruitment.…”
Section: Matrix Metalloproteinasessupporting
confidence: 56%
“…IHC was used to further evaluate the involvement of CD40 in OLP with results showing strong intensity of CD40 staining in OLP tissues . Overall, the results of this study strongly suggest that CD40 and CD86 may play an important pathophysiologic role in oral inflammatory diseases like OLP …”
Section: Immunopathogenesis Of Olpmentioning
confidence: 61%
See 3 more Smart Citations